2001
DOI: 10.1002/jbt.10010
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivities of plant and animal mitochondria to the herbicide paraquat

Abstract: Paraquat herbicide is toxic to animals, including humans, via putative toxicity mechanisms associated to microsomal and mitochondrial redox systems. It is also believed to act in plants by generating highly reactive oxygen free radicals from electrons of photosystem I on exposure to light. Paraquat also acts on non-chlorophyllous plant tissues, where mitochondria are candidate targets, as in animal tissues. Therefore, we compared the interaction of paraquat with the mitochondrial bioenergetics of potato tuber,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 45 publications
(92 reference statements)
2
42
1
Order By: Relevance
“…For controls, herbicides alone were tested for spectroscopic interferences of fluorescein measurement at 458 nm, and no effects were detected (data not shown). fractions (Vicente et al, 2001) previously showed no sensitivity of swelling dependent on permeabilization to H + (even with 30 mM paraquat), in contrast with H + permeabilization induced by 2,4-D and dicamba (Peixoto et al, 2004). These results indicate the capability of 2,4-D and dicamba to disrupt the membrane integrity, probably as a consequence of perturbation of membrane structure upon partition of the herbicides.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…For controls, herbicides alone were tested for spectroscopic interferences of fluorescein measurement at 458 nm, and no effects were detected (data not shown). fractions (Vicente et al, 2001) previously showed no sensitivity of swelling dependent on permeabilization to H + (even with 30 mM paraquat), in contrast with H + permeabilization induced by 2,4-D and dicamba (Peixoto et al, 2004). These results indicate the capability of 2,4-D and dicamba to disrupt the membrane integrity, probably as a consequence of perturbation of membrane structure upon partition of the herbicides.…”
Section: Resultsmentioning
confidence: 71%
“…Furthermore, it has also been shown that plant mitochondria are better protected at the antioxidant level, but still susceptible to paraquat toxicity (Vicente et al, 2001;Peixoto et al, 2004). All the herbicides tested deplete ATP and ADP with a correspondent increase of AMP (data not shown).…”
Section: Article In Pressmentioning
confidence: 84%
See 1 more Smart Citation
“…A mutant allele of FRIENDLY (noxy38) was identified in a screen for insensitivity to the oxylipin pathogen defense mediator 9-hydroxy-10,12, 15-octadecatrienoic acid in Arabidopsis (Vicente et al, 2001;Vellosillo et al, 2013). The noxy38 mutant showed an up-regulation of alternative oxidase expression and a decreased capacity to fight bacterial infection (Vellosillo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies of the effect of paraquat on mitochondrial bioenergetics of rat liver and potato mitochondria confirmed the protonophoric action of herbicide on both mitochondrial membranes. However, the sensitivity of potato tuber mitochondria to paraquat was lower than that of rat liver mitochondria (Vicente et al, 2001). Differences between rat liver and potato tuber mitochondria were also observed on the effects of paraquat on both ΔΨ and oxygen consumption of complex-I-dependent respiration.…”
Section: Paraquatmentioning
confidence: 81%